A case study on Mummified Foetus in a heifer - Azizunnesa, M; Sutradhar, BC; Das, BC; Hossain, MF; Faruk, MO (University Journal of Zoology, Rajshahi University, 2010)
DOI: 10.3329/ujzru.v28i0.5289 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 61-63